A poesia essencial e o sublime nos anos 1930 - Simpson, Pablo [UNESP] (My University, 2012)
This  paper  attempts  to  investigate  a  part of  Brazilian’s modernism poetic tradition starting  from the notions of “sublime”,”essential poetry” and “pure poetry”. Such notions seem to constitute both the critical projects of Alceu Amoroso Lima and Graça Aranha, as well as they allow to consider partially the trajectories of Joaquim Cardozo, Emílio Moura, Henriqueta Lisboa and Augusto Frederico Schmidt in face of the vanguards.

Este ensaio pretende investigar uma parte da tradição poética modernista brasileira a partir das noções de “sublime”, de “poesia essencial” e de “poesia pura”. Tais noções parecem constituir projetos críticos como os de Alceu Amoroso Lima e Graça Aranha, bem como possibilitam considerar parcialmente as trajetórias de Joaquim Cardozo, Emílio Moura, Henriqueta Lisboa e Augusto Frederico Schmidt em face das vanguardas.
Keywords: Poesia brasileira do século XX; Modernismo brasileiro; Sublime; Poesia essencial; Brazilian’s modernism; Poetry; Sublime